2009
DOI: 10.1007/s10658-009-9494-3
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium head blight (FHB) in Flanders: population diversity, inter-species associations and DON contamination in commercial winter wheat varieties

Abstract: The presence of Fusarium spp. causing Fusarium head blight (FHB) of wheat was studied in Flanders (Belgium) in 2007 and 2008. Symptoms, deoxynivalenol content (DON), Fusarium spp. and trichothecene chemotypes were determined at seven locations on different commercial wheat varieties. Overall, significant differences in disease pressure between locations and varieties were observed within 1 year. In addition, we were able to detect consistent and significant resistance differences among the common varieties bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 34 publications
10
59
1
Order By: Relevance
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionsupporting
confidence: 61%
“…The 3- isolates belonging to population 2 were included in the analysis of aggressiveness, ten of these were included in the growth rate analysis c 17 3-ADON isolates were included in the analysis of aggressiveness, 16 of these were included in the growth rate analysis ADON chemotype also predominated among a small set of FGSC isolates from an earlier collection of Norwegian cereals (Langseth et al 1999(Langseth et al , 2001, and was found in oat and wheat samples collected between 2009 and 2011 in Sweden, whereas the 15-ADON chemotype was not observed (Fredlund et al 2013;Lindblad et al 2013 (Nielsen et al 2012). Our data add to a growing set of studies indicating a geographical partitioning of trichothecene types (chemotypes or genotypes) throughout Europe, with 3-ADON dominating in Northern Europe, whereas 15-ADON appears predominant in the Western and Southern Europe including the UK (Jennings et al 2004), Belgium (Audenaert et al 2009), Italy (Prodi et al 2009;Somma et al 2014), Luxembourg (Pasquali et al 2010), Poland (Stępień et al 2008), Hungary (Toth et al 2005), Germany (Talas et al 2011), and France (Boutigny et al 2014). …”
Section: Discussionsupporting
confidence: 61%
“…Fusarium head blight (FHB) is an important disease in cereals caused by a complex of Fusarium spp., of which the hemibiotroph F. graminearum is one of the most prevalent (Parry et al, 1995;Goswami and Kistler, 2004;Audenaert et al, 2009). Besides yield losses of up to 40%, FHB also confers quality losses because of the production of mycotoxins such as deoxynivalenol (DON; Parry et al, 1995;Bottalico and Perrone, 2002;Vanheule et al, 2014).…”
mentioning
confidence: 99%
“…The present samples included no NIV producing isolates. Talas et al (2011) also detected only 1.2% NIV producing isolates in neighbouring Germany, although low to medium frequencies of this chemotype have been recorded in Europe (Stepien et al 2008;Audenaert et al 2009;Prodi et al 2009). The analysis of a larger collection of Czech F. graminearum isolates would probably reveal a frequency of NIV producers that comparable to detected in Germany.…”
Section: Resultsmentioning
confidence: 92%